AKT1 induces Nanog promoter in a SUMOylation-dependent manner in different pluripotent contexts - Francia, Marcos Gabriel (2023)
AKT/PKB is a kinase crucial for pluripotency maintenance in pluripotent stem cells. Multiple post-translational modifications modulate its activity. We have previously demonstrated that AKT1 induces the expression of the pluripotency transcription factor Nanog in a SUMOylation-dependent manner in mouse embryonic stem cells. Here, we studied different cellular contexts and main candidates that could mediate this induction. Our results strongly suggest the pluripotency transcription factors OCT4 and SOX2 are not essential mediators. Additionally, we concluded that this induction takes place in different pluripotent contexts but not in terminally differentiated cells. Finally, the cross-matching analysis of ESCs, iPSCs and MEFs transcriptomes and AKT1 phosphorylation targets provided new clues about possible factors that could be involved in the SUMOylation-dependent Nanog induction by AKT.